From Xerox to Pdf: Juan Luis Martinez and Tan Lin - Cussen-Abud, F (UNIV AUSTRAL CHILE, 2016)
In this essay I ll reflect on the possibilities of literary appropriation related to xerox and computer technologies. I will analyze two cases from very different cultural contexts. The first is the posthumous book El poeta anonimo, by Juan Luis Martinez, developed throughout the 80s, and composed almost entirely of photocopies of other books, magazines and newspapers. The second is two recent works of American poet Tan Lin, Seven Controlled Vocabularies and Obituary 2004. The Joy of Cooking, which includes scanned photographs, documents and objects, and Heath, which takes a lot of material from websites. Both authors are close to the notion of the poet as a "remixer" proposed by Vilem Flusser, but also try to show the loss that involves cutting, copying and pasting.